Effect of nitrogen management and seedling raising methods on the productivity of Aus rice under tidal ecosystem of Bangladesh - Antara Sarker; Swadesh Chandra Samanta; Gopal Saha (Hasanuddin University, 2020)
The low productivity of Aus rice in the tidal ecosystem of Bangladesh is mainly due to the difficulties in nitrogen (N) management under high tidal water along with unavailability of irrigation water during the onset of rice cultivation. Our present study demonstrated how the productivity of Aus rice could be improved using appropriate seedling raising methods and N management practices. The study was laid out in split plot design consisting two factors viz., seedling raising methods (wet seed bed and dry seed bed) and N management practices (six N treatments) in three replications. Results indicated that both the seedling raising methods and N management practices had significant effect on all the yield contributing characters of transplanted Aus rice under tidal condition. Specifically, the combination of seedlings raised in wet seed bed and fertilized with urea super granule (USG) at 10 days after transplanting (DAT) i.e., N3W showed the best values for plant height (110.33cm), number of effective tillers hill-1 (14.60), days required 50% flowering (53.00 DAT), days to maturity (84.33 DAT), panicle length (23.37 cm), number of filled grain panicle-1 (88.13), 1000-grain weight (43.17 g), grain yield (4.62 tha-1), straw yield (6.07 tha-1), biological yield (10.67 tha-1), and harvest index (43.17%). However, in considering the productivity/ grain yield, besides N3W, the whole urea application at land preparation along with wet seed bed (N1W) and USG application along with dry seed bed (N3D) also produced statistically similar results (p<0.01) and thus all these three combinations may be practiced for improving productivity and ensuring horizontal expansion of Aus rice in the tidal ecosystem of Bangladesh.